Pengaruh Transformational Leadership, Entrepreneur Orientation, Dan Innovation Terhadap Sme’s Performance - Louis Hans Joshua; F.X. Kurniawan Tjakrawala (Jurnal Ekonomi, 2022)
The aims of this study is to determine the effects of transformational leadership, entrepreneur orientation, and innovation on SMEs Performance in culinary sub-sector moderated with environmental dynamism. The samples of this study is taken using purposive sampling technique and the sample that meets the criteria is 165 out of 174 total respondent. Data gathering is done using google forms and data processing is done using SPSS version 28.0.1.0 and SmartPLS version 3.3.5. The result of this study shows that transformational leadership, entrepreneur orientation, and innovation positively and significantly affect SMEs performance, while environmental dynamism shows that it can moderate the effect of transformational leadership, entrepreneur orientation, and innovation on SMEs performance. Implication that emerge from this study is the importance of leader’s role and capability in running their business in order to increase its performance.